Effect of Shakthi bandhasanas on Primary Dysmenorrhea - A Study Protocol of a Randomized Controlled Trial - Kanimozhi, Ramu; Gayathri, Annamalai; Kumaresan, Poornachandran; Sathiyanandham, Muniyappan; Jeevajothi, Chellapandiyan; Naveena, Arumugam; Radhika, Loganathan (Indian Journal of Integrative Medicine, 2024)
Primary dysmenorrhea (PD) is recurrent lower abdominal pain that happens during the menstrual cycle and is not associated with anyother pelvic pathology. In India prevalence of dysmenorrhea is 87.87% and incidence is 33.5% among adolescent girls. Yoga see ms tobe effe ctive in regulating the various physiological functions. Shakthi bandasanas is a dynamic group of asanas which may haveeffect on abdominal region. Hence, we have planned this study to find the effect of shakthi bandasanas on primary dysmenorrhoea. Atotal of 80 subjects between 14 to 25 years will be recruited. This study adopted a randomized controlled trial. Study has 2 groupswith 40 subjects in each group. Study group subjects will be recommended to practice shakthi bandasanas and control group will berest in supine position for 21 days. Baseline and post intervention assessments will be done for all subjects. Outcome variab les areMenstrual symptom Questionnaire and Visual Analogue Scale. Data will be analysed using the Statistical Package for Social Sciences.Version 16. In this study, we will consider p (probability) value of 0.05 to be statistically significant. The result will be represented inbar diagram using the mean value of the dependent variables. If this study provides significant ch anges, then shakthi bandasanas maybe adjuvant therapy in the management of primary dysmenorrhea. Ethical clearance was obtained (IEC IIYNMS/Approval/014/2023)and registered in a clinical trial (CTRI/2023/10/059308).